Multi-bound-dependent fault-tolerant control for flexible spacecraft against partial actuator failures - Lei, Furong; Zhang, Bin; Li, Tao (Chinese Control Conference, 2016)
In this paper, a multi-bound-dependent fault tolerant attitude control scheme is achieved of flexible spacecraft with time delay and actuator failures. This designed control algorithm is delay-dependent and actuator effectiveness coefficient-dependent simultaneously. Moreover, it also is shown that the algorithm can not only guarantee the closed-loop system to be stable with attenuation level, but also be able to tolerate partial loss of actuator effectiveness. The proposed controller design algorithms are obtained by combining free weighting matrices method with a new delay integral inequality technique. The effectiveness of the proposed design method is demonstrated in a spacecraft attitude control system subject to loss of actuator effectiveness.